Lakon “ Dhanaraja” - Andi Wicaksono (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2012)
Karya ini mengajak masyarakat untuk menyikapi kerasnya kehidupan dengan konsep hidup orang jawa, yakni “Urip sadêrma nglakoni“, yang didasari semangat “Wong têmên bakalé kêtêmu”, dan diiringi dengan kesadaran bahwa “Urip manungsa pinasthi ing Pangéran”. Konsep hidup tersebut, selanjutnya ditransformasikan ke dalam lakon wayang dan pertunjukannya. Karya ini mentrasformasikan secara tepat konsep tersebut ke dalam lakon. Lakon yang dipilih adalah lakon “Alap-alapan Sukèsi” dan “Bêdhahing Lokapala” yang diramu menjadi satu lakon utuh dengan memfokuskan tokoh Prabu Dhanaraja. Penggubahan lakon “ Dhanaraja” diaktualisasikan ke dalam pertunjukan yang berdurasi waktu kurang lebih tiga jam. Karya ini memaparkan bagaimana cara meramu dua lakon menjadi satu dalam struktur yang utuh tanpa terlihat sekedar menempel, serta dengan mentranformasikan konsep “Urip sadêrma nglakoni“, yang didasari semangat “Wong têmên bakalé kêtêmu”, dan diiringi dengan kesadaran bahwa “Urip manungsa pinasthi ing Pangéran” ke dalamnya. Hal tersebut dilakukan dengan cara membangun konfl ik dan dramatika dalam rangkaian cerita yang disajikan.Kata kunci: lakon, Dhanaraja, struktur dramatik, dramaturgi wayangABSTRACTThe story of Dhanaraja. This work is aimed to invite people responding the severe life with Javanese’s life concept,that is “Urip sadêrma nglakoni’ (let the life fl ow), and that is based on the spirit of “Wong têmên bakalé kêtêmu” (successcan be achieved by hardworking and being honest), and that is also accompanied by an awareness that “Urip manungsapinasthi ing Pangéran” (people’s life is based on the destiny which has already arranged by God). This Javanese’s lifeconcept, then, is transformed into the wayang story and its performance. This work has truly transformed the conceptinto a performance. The chosen performances are “Alap-Alap Sukesi” and “Bedhading Lokapala” which are managedinto a whole performance focusing on King Dhanuraja character. The composing story of Dhanaraja is actualized into athree-hour-performance. This work describes how to manage two stories into one complete structure without merely seenby attaching the stories, and also by transforming the concept of “Urip sadêrma nglakoni” (let the life fl ow), that is basedon the spirit of “Wong têmên bakalé kêtêmu” (success in life can be achieved by hardworking and being honest ), andaccompanied by an awareness that “Urip manungsa pinasthi ing Pangéran” (people’s life is based on the destiny which hasalready arranged by God) into the performance. These previous things are carried out by developing the confl ict and thedramatic sequence order of play performance.Keywords: story, Dhanaraja, a dramatic structure, a wayang dramaturgy